2012
DOI: 10.2147/cia.s37158
|View full text |Cite
|
Sign up to set email alerts
|

Higher estimates of daily dietary net endogenous acid production (NEAP) in the elderly as compared to the young in a healthy, free-living elderly population of Pakistan

Abstract: Dietary intake has been shown to influence the acid–base balance in human subjects; however, this phenomenon is poorly understood and rarely reported for the least well-studied segment of older people in a developing country. The aims of the present study were to: (1) quantify estimates of daily net endogenous acid production (NEAP) (mEq/d) in a sample of otherwise healthy elderly aged 50 years and above; and (2) compare NEAP between the elderly and young to determine the effects of aging, which could contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…No studies were excluded based on quality of study, although many studies did not report sufficient information for a clear bias assessment. All studies, except four [ 26 , 45 , 46 , 50 ], reported inclusion and/or exclusion criteria, and stated that the participants met these criteria. Of the studies measuring energy intake (49 studies), 18 studies matched the younger and older participants for body weight [ 23 , 26 , 27 , 29 , 30 , 35 , 40 , 45 , 51 , 52 , 54 , 58 , 63 , 69 , 70 , 72 , 76 , 80 ] and 13 studies for BMI [ 26 , 27 , 33 , 40 , 41 , 42 , 45 , 47 , 48 , 49 , 58 , 68 , 76 ] and 11 studies considered gender as a confounder [ 31 , 39 , 43 , 46 , 47 , 52 , 56 , 71 , 75 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No studies were excluded based on quality of study, although many studies did not report sufficient information for a clear bias assessment. All studies, except four [ 26 , 45 , 46 , 50 ], reported inclusion and/or exclusion criteria, and stated that the participants met these criteria. Of the studies measuring energy intake (49 studies), 18 studies matched the younger and older participants for body weight [ 23 , 26 , 27 , 29 , 30 , 35 , 40 , 45 , 51 , 52 , 54 , 58 , 63 , 69 , 70 , 72 , 76 , 80 ] and 13 studies for BMI [ 26 , 27 , 33 , 40 , 41 , 42 , 45 , 47 , 48 , 49 , 58 , 68 , 76 ] and 11 studies considered gender as a confounder [ 31 , 39 , 43 , 46 , 47 , 52 , 56 , 71 , 75 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies were conducted in the United States [ 20 , 21 , 27 , 28 , 29 , 31 , 35 , 39 , 40 , 42 , 46 , 50 , 53 , 55 , 58 , 59 , 60 , 62 , 63 , 70 , 72 , 73 , 74 , 75 , 78 , 79 , 80 ], 10 in Europe [ 41 , 44 , 45 , 54 , 56 , 67 , 71 , 76 , 77 , 81 ], eight in Australia [ 23 , 34 , 47 , 48 , 49 , 68 , 69 ], two in Asia [ 26 , 43 ], two in Canada [ 51 , 52 ], and one in Chile [ 30 ]. The oldest study was published in 1966 [ 50 ] and the most recent in 2014 [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…How these selfish behaviors of the immune system and brain can be exploited in old age. As we have previously reported that the aged are already having a malfunctioning in their energy metabolism and energy allocation mechanism [89], more prone to pro-inflammatory diets [90], disturbed by changes in their body composition [91] and have compromised immunity [92]…”
Section: Final Words and Future Outlooksmentioning
confidence: 99%